Monitoring of Sound and Carious Surfaces under Sealants over 44 Months. (November 2014) - Fontana, M.; Platt, J.A.; Eckert, G.J.; González-Cabezas, C.; Yoder, K.; Zero, D.T.; Ando, M.; Soto-Rojas, A.E.; Peters, M.C.
Although there is strong evidence for the effectiveness of sealants, one major barrier in sealant utilization is the concern of sealing over active caries lesions. This study evaluated detection and monitoring of caries lesions through a clear sealant over 44 mo. Sixty-four 7- to 10-year-old children with at least 2 permanent molars with International Caries Detection and Assessment System (ICDAS) scores 0-4 (and caries less than halfway through the dentin, radiographically) were examined with ICDAS, DIAGNOdent, and quantitative light-induced fluorescence (QLF) before sealant placement and 1, 12, 24, and 44 mo (except QLF) after. Bitewing radiographs were taken yearly. DIAGNOdent and QLF were able to distinguish between baseline ICDAS before and after sealant placement. There was no significant evidence of ICDAS progression at 12 mo, but there was small evidence of minor increases at 24 and 44 mo (14% and 14%, respectively) with only 2% ICDAS ≥ 5. Additionally, there was little evidence of radiographic progression (at 12 mo = 1%, 24 mo = 3%, and 44 mo = 9%). Sealant retention rates were excellent at 12 mo = 89%, 24 mo = 78%, and 44 mo = 70%. The small risk of sealant repair increased significantly as baseline ICDAS, DIAGNOdent, and QLF values increased. However, regardless of lesion severity, sealants were 100% effective at 12 mo and 98% effective over 44 mo in managing occlusal surfaces at ICDAS 0-4 ( i.e., only 4 of 228 teeth progressed to ICDAS ≥ 5 associated with sealants in need of repair and none to halfway or more through the dentin, radiographically). This study suggests that occlusal surfaces without frank cavitation (ICDAS 0-4) that are sealed with a clear sealant can be monitored with ICDAS, QLF, or DIAGNOdent, which may aid in predicting the need for sealant repair.